Agriculture and nutrition in India: Mapping evidence to pathways - Kadiyala, Suneetha; Harris, Jody; Headey, Derek D.; Yosef, Sivan; Gillespie, Stuart (Wiley, 2014)
In India, progress against undernutrition has been slow. Given its importance for income generation, improving diets, care practices, and maternal health, the agriculture sector is widely regarded as playing an important role in accelerating the reduction in undernutrition. This paper comprehensively maps existing evidence along agriculture–nutrition pathways in India and assesses both the quality and coverage of the existing literature. We present a conceptual framework delineating six key pathways between agriculture and nutrition. Three pathways pertain to the nutritional impacts of farm production, farm incomes, and food prices. The other three pertain to agriculture–gender linkages. After an extensive search, we found 78 research papers that provided evidence to populate these pathways. The literature suggests that Indian agriculture has a range of important influences on nutrition. Agriculture seems to influence diets even when controlling for income, and relative food prices could partly explain observed dietary changes in recent decades. The evidence on agriculture–gender linkages to nutrition is relatively weak. Sizeable knowledge gaps remain. The root causes of these gaps include an interdisciplinary disconnect between nutrition and economics/agriculture, a related problem of inadequate survey data, and limited policy‐driven experimentation. Closing these gaps is essential to strengthening the agriculture sector's contribution to reducing undernutrition.